Study of Negative Permittivity in Nanosized LaNiO3 for Electromagnetic Interference Shielding: A Modified Drude Model Approach - Katheriya T.; Nirala G.; Upadhyay S. (My University, 2025)
Addressing the growing concern of electromagnetic (EM) pollution requires the development of advanced electromagnetic interference (EMI) shielding materials. This study investigates the epsilon-negative (ENG) behavior of nanosized LaNiO3, highlighting its potential as a reflective shield for EMI and as an alternative to conventional metal-based composites in stealth and shielding applications. LaNiO3 was synthesized by the sol-gel method, and its phase purity was confirmed via X-ray diffraction. Electrical characterization revealed consistent ENG behavior [ϵr′ ∼ (22.32 ± 0.11) × 106] and metallic conductivity (σtotal ∼ 131 S/m) across 100 Hz to 1.5 MHz and up to 300 °C. The Drude model was initially applied to fit the experimental data; however, a significant mismatch between the theoretical model and the experimental results encouraged us to refine the theoretical approach by incorporating a term for displacement current, which had been neglected in the original Drude model. By fitting the modified Drude model to the experimental data points, we calculated the plasma frequency [ωp ∼ (3.09 ± 0.46) GHz] and damped frequency (ωτ ∼ 1.57 MHz). Impedance studies showed a negative phase angle (φ) and an upward trend in the Nyquist plot (Z″ vs Z′), demonstrating an inductive nature for LaNiO3. Microwave measurements demonstrated a shielding effectiveness (SE) of ∼33 dB, primarily due to reflection resulting from impedance mismatch. The findings demonstrated that LaNiO3 could be a promising candidate for EMI shielding in reflection mode. © 2025 American Chemical Society.